Cardiac Resynchronization Therapy Outcomes in Type 2 Diabetic Patients: Role of MicroRNA Changes - Celestino Sardu; Michelangela Barbieri; Maria Rosaria Rizzo; Pasquale Paolisso; Giuseppe Paolisso; Raffaele Marfella (Journal of Diabetes Research)
Heart failure (HF) and type 2 diabetes mellitus (T2DM) are two growing and related diseases in general population and particularly in elderly people. In selected patients affected by HF and severe dysfunction of left ventricle ejection fraction (LVEF), with left bundle brunch block, the cardiac resynchronization therapy with a defibrillator (CRT) is the treatment of choice to improve symptoms, NYHA class, and quality of life. CRT effects are related to alterations in genes and microRNAs (miRs) expression, which regulate cardiac processes involved in cardiac apoptosis, cardiac fibrosis, cardiac hypertrophy and angiogenesis, and membrane channel ionic currents. Different studies have shown a different prognosis in T2DM patients and T2DM elderly patients treated by CRT-D. We reviewed the literature data on CRT-D effect on adult and elderly patients with T2DM as compared with nondiabetic patients.